The development of low-cost spin coater with wireless IoT control for thin film deposition - Ahmad Muhajer Abdul Aziz; Muhammad Idzdihar Idris; Zul Atfyi Fauzan Mohammed Napiah; Muhammad Noorazlan Shah Zainudin; Marzaini Rashid; Luke Bradley (Institute of Advanced Engineering and Science, 2024)
A low-cost spin coater with a wireless remote system that can deposit thin films of uniform thickness and quality at a significantly lower cost than traditional methods. The system consists of three main parts, a motorized spindle, a spin-coating head, and a control system connected to the network. The mechanical design on the mechanical part, spin coater system design with ESP32, and implementation of wireless control through visual basic. The network-enabled control system allows for real-time monitoring and adjustment of the deposition process, which can improve efficiency and reproducibility. This low-cost spin coating system represents a promising solution for organizations seeking to access thin film deposition technology at a fraction of the cost of traditional systems. By integrating wireless IoT control into low-cost spin coaters, the impact of this technology on coating uniformity will provide valuable insights for future advancements in this field.